2001
DOI: 10.1007/bf03033212
|View full text |Cite
|
Sign up to set email alerts
|

Induction of 78 kD glucose-regulated protein (GRP78) expression and redox-regulated transcription factor activity by lead and mercury in C6 rat glioma cells

Abstract: Lead (Pb) and mercury (Hg) are widespread environmental contaminants that induce prominent neural toxicity. Although the brain is not the major Pb and Hg depot in the body, these metals preferentially accumulate in astroglia to exert toxic effects. In this study, we examined the effects of Pb acetate and HgCl(2) on the expression of GRP78, a molecular chaperone in the endoplasmic reticulum (ER) that may provide cytoprotection in response to cellular stresses in the C6 rat glioma cell line. We also evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Upregulation of the expression of stress proteins, such as HSP70 may play a role in the underlying mechanisms of hormesis (Damelin et al 2000). Qian et al (2001) demonstrated the hormetic effects of lead and mercury on Grp78 mRNA in C6 rat glioma cells. Low-level inorganic mercury also transcriptionally activated Grp78 in HepG2 cells (Sutton et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of the expression of stress proteins, such as HSP70 may play a role in the underlying mechanisms of hormesis (Damelin et al 2000). Qian et al (2001) demonstrated the hormetic effects of lead and mercury on Grp78 mRNA in C6 rat glioma cells. Low-level inorganic mercury also transcriptionally activated Grp78 in HepG2 cells (Sutton et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that some heavy metals, including manganese, lead and mercury, may induce ER stress and contribute to cellular damage in the brain (Chun et al 2001;Qian et al 2001). Similarly, cadmium also has the potential to induce ER stress in various cell types.…”
Section: Evidence For Induction Of Er Stress By Cadmiummentioning
confidence: 99%
“…Based on the fact that ER stress is located downstream of oxidative stress, these chemical chaperones should be useful for prevention and treatment of cadmiuminduced toxicity. In addition, several other heavy metals including manganese, lead, mercury, copper, nickel and cobalt also have the potential to induce ER stress in renal tubular cells and other cell types Chun et al 2001;Qian et al 2001). The similar mechanism described here could be involved in other metal-induced toxicity, and chemical chaperoning might be a strategy for the treatment of various heavy metal intoxication.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…For example, manganese, lead and mercury induced expression of 78 kDa glucose-regulated protein (GRP78), a marker of ER stress, in cultured dopaminergic neuronal cells, astrocytes and glioma cells, respectively. [16][17][18] Recently, it has been reported that ER stress was involved in paracetamol-and cisplatin-induced apoptosis of renal tubular cells. 19,20 However, roles of ER stress in cadmium-induced renal tubular injury have not been disclosed yet.…”
mentioning
confidence: 99%